Plant SUMO E3 Ligases: Function, Structural Organization, and Connection With DNA - Jmii, Souleimen; Cappadocia, Laurent (Frontiers in Plant Science, 2021)
Protein modification by the Small Ubiquitin-like MOdifier (SUMO) plays an important role in multiple plant processes, including growth, development, and the response to abiotic stresses. Mechanistically, SUMOylation is a sequential multi-enzymatic process where SUMO E3 ligases accelerate SUMO conjugation while also influencing target identity and interactions. This review explores the biological functions of plant SUMO E3 ligases (SIZs, MMS21s and PIALs) in relation to their molecular activities and domains. We also explore the sub-cellular localization of SUMO E3 ligases and review evidence suggesting a connection between certain SUMO E3 ligases and DNA that contributes to gene expression regulation.